Disconnection time and sequence of rooftop PVs under short-circuit faults in low voltage networks - Yengejeh, H.; Shahnia, F.; Islam, Syed (2015)
This paper presents an analysis on the disconnection time of single-phase rooftop PVs, located in a three-phase four-wire low voltage distribution feeder after a line-to-ground short-circuit fault on the low voltage feeder. The paper aims to evaluate and discuss the disconnection time and sequence of PVs in a network with 100% PV penetration level. The impact of different parameters such as the location of the fault, impedance of the fault and the ratio of PVs generation capacity to the load demand are considered. Furthermore, the effect of the system earthing in the form of multiple earthed neutral and non-effectively grounded systems are evaluated on the PVs disconnection time. The analyses intend to figure out the conditions under which the PVs in the feeder may fail to disconnect after a line-to-ground fault and keep feeding the fault. The analyses are carried out in PSCAD/EMTDC software.